Pengaruh Disiplin terhadap Kinerja Pegawai pada Badan Perpustakaan dan Arsip Daerah Provinsi Kepulauan Riau - ALDO SEPTAMA PUTRA; TUTI KHAIRANI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Badan Perpustakaan dan Arsip Daerah Provinsi Kepulauan Riau, is a goverment's organization that works on library's service field, ranging on script to non-script, on archives development to archives maintenance field. Which has duties to establishing and performing the technical policy in the regional archives and library, and implementing the deconcentration and assistance duties which has given by Governor due to the duties scope. However in the implementation, the violation of discipline and unsatisfactory performance still can be found. The human resource on library and archieves field who always ready to perform the main tasks and function as a professional is still on demand. Therefore, the employees of Badan Perpustakaan dan Arsip Daerah Provinsi Kepulauan Riau is required to work in discipline in order to get a great performance. The legality listed in the form of "Peraturan Pemerintah No. 53 tahun 2010" about "Disiplin Pegawai Negeri Sipil".Key Word: Impact, Affect, Influence, Discipline, Performance, Employee.